Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

A few definitions:

A Submodular function $ f:2^E \rightarrow R $ is a function that satisfies the following two equivalent definitions:

  • for every $ S,T\subseteq E: f(S) + f(T) \geq f(S\cup T)+f(S\cap T) $
  • for every $ S,T\subseteq E $ with $ S\subseteq T $ and for every $ x\in E\setminus T : f(S\cup \{x\})-f(S)\geq f(T\cup\{x\}) - f(T) $

A monotone submodular function is a submodular functions such that for every $ S,T \subseteq E $ with $ S\subseteq T : f(T)\geq f(S) $ . We also define $ f(\emptyset) = 0 $.

Show that $ \sum_{i=1}^n(f(S)-f(S-\{e_i\})\leq f(S) $ where $ e_i\in S $ for all i, where f is a monotone submodular function.

share|improve this question
add comment

2 Answers

up vote 1 down vote accepted

The formula $ \sum_{i=1}^n(f(S)-f(S-\{e_i\})\leq f(S) $ is certainly false.If $f$ is a (monotone) submodular function, then $f+c$ with $c \in \mathbb R$ is also a (monotone) submodular function. So you would have $ \sum_{i=1}^n(f(S)-f(S-\{e_i\})\leq f(S) + c$ for arbitrary $c \in \mathbb R$, which is obviously not true.

However, it's easy to prove $ \sum_{i=1}^n(f(S)-f(S-\{e_i\})\leq f(S) - f(\emptyset) $. Simply note that $f(S)-f(S-\{e_i\}) \leq f(S-U)-f(S-U-\{e_i\})$ for $e_i\notin U$. So the sum is bounded by a telescope sum: $$ \sum_{i=1}^n(f(S)-f(S-\{e_i\})\leq \\ (f(S)-f(S-\{e_1\}))+(f(S-\{e_1\}))-f(S-\{e_1, e_2\})+\ldots+(f(S-\cup_{i=1}^{n-1} \{e_i\})-f(S-\cup_{i=1}^n \{e_i\}))\\ =f(S)-f(S-\cup_{i=1}^n \{e_i\}) \leq f(S) - f(\emptyset)$$ Only the last step of replacing $f(S-\cup_{i=1}^n \{e_i\})$ by $f(\emptyset)$ requires monotony.

share|improve this answer
    
Sorry, forgot to mention that f(empty_set) = 0. You're right of course. –  Shmoopy Dec 10 '12 at 9:24
add comment

Fix a set $E$ with monotone submodular function $f$. Note that $\tilde{f}(I) := f(I) + \lambda$ also will be a monotone submodular function, for any $\lambda \in \mathbb{R}$, since loosely speaking the same number of $\tilde{f}$'s appear on each side of all inequalities.

With that for $n = 1$ our desired inequality just reads $f(S - e_1) \geqslant 0$, but by our analysis this can be taken to be arbitrary, in particular negative.

So perhaps you want some further hypothesis?

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.